An Innovative Corn to Silage-Grass-Legume Intercropping System With Oversown Black Oat and Soybean to Silage in Succession for the Improvement of Nutrient Cycling - Pariz, Cristiano Magalhães [UNESP]; Costa, Nídia Raquel [UNESP]; Costa, Ciniro [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; de Castilhos, André Michel [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; Calonego, Juliano Carlos [UNESP]; Andreotti, Marcelo [UNESP]; Souza, Daniel Martins de [UNESP]; Cruz, Igor Vilela [UNESP]; Longhini, Vanessa Zirondi [UNESP]; Protes, Verena Micheletti [UNESP]; et al. (Frontiers, 2020)
In the context of sustainable tropical agriculture, an innovative corn (Zea mays L.) to silage-grass-legume intercropping system can promotes plant diversity, improves agronomic performance and land-use efficiency, and increases the yield of oversown black oat (Avena strigosa Schreb) and soybean [Glycine max (L.) Merr.] to silage in succession. Thus, during three growing seasons on a Typic Haplorthox in Botucatu, São Paulo State, Brazil, four treatments of a corn to silage production system were implemented in summer/autumn with black oat oversown in winter/spring: (1) corn intercropped with palisade grass (Urochloa brizantha “Marandu”) and black oat overseeded in lines; (2) corn intercropped with palisade grass and black oat overseeded in a broadcast system with superficial incorporation; (3) corn intercropped with palisade grass + pigeon pea [Cajanus cajan (L.) Millsp.] and black oat overseeded in lines; and (4) corn intercropped with palisade grass + pigeon pea and black oat overseeded in a broadcast system with superficial incorporation. During winter/spring, the black oat pastures were grazed by lambs, but results on forage allowance and nutritive value for animal grazing and on animal performance are not reported in the present manuscript. In the fourth growing season, the effect of soybean to silage intercropped with guinea grass (Panicum maximum “Aruana”), with only a residual effect of the four production systems from the previous three growing seasons, was evaluated. Despite greater interspecific competition of palisade grass and pigeon pea intercropped with corn, this more complex system produced better results. Thus, when analyzing this system as a whole, the triple intercrop (corn + pigeon pea + palisade grass) combined with oversown black oat in lines was the most effective option for silage production and for the improvement of other elements of system productivity, such higher surface mulch quantity, leaf nutrient concentrations, and yield of soybean to silage intercropped with guinea grass. This intercrop also generated better nutrient cycling because an increased quantity of nutrients was retained in standing plant residue and surface mulch, which resulted in better land- and nutrient-use efficiency, with an emphasis on nitrogen and potassium.
Keywords: Cajanus cajan; integrated crop-livestock systems; land use efficiency; Urochloa brizantha; Zea mays